Consumer’s Personal and Social Factors on Purchase Intentions of Counterfeit Luxury Products - Ganbold, Munkhbayasgalan; Gantulga, Urandelger (Jurnal Ilmiah Peuradeun, 2023)
There are several studies to answer the question of why consumers make purchases of counterfeit luxury goods. However, researchers have not studied the impact of consumer’s personal and social factors on purchasing counterfeit luxury products yet. The current study examines how consumers’ personal (face and public self-consciousness) and social factors (informative and normative suspective) influence their purchase intention towards counterfeit luxury products. Quantitative research methodology was used to measure consumers’ buying behavior of counterfeit luxury products by conducting an online survey of 254 consumers. The collected data were further analyzed by SPSS-28 and SMART-PLS 4 software. The findings indicate that social factors, such as informational susceptibility, strongly influence the purchase intention of counterfeit luxury products. Furthermore, consumer personal factors such as public self and face consciousness significantly influence fake luxury product purchasing intention. This study has implications for firms that import luxury goods and policymakers responsible for creating policies and marketing plans to deter consumers from buying counterfeit luxury goods.